Seasonal dynamics of the planktonic community in Lake Druzhby, Princess Elizabeth Land, Eastern Antarctica - Laybourn-Parry, J; Bayliss, P (1996)
1. The temporal abundance and composition of the plankton of a continental Antarctic lake (Lake Druzhby) situated in the Vestfold Hills, Eastern Antarctica was investigated from December 1992 to December 1993. The system was dominated by microbial plankton (cyanobacteria, heterotrophic bacteria and protozoans) with few metazoans. 2. Chlorophyll a concentrations ranged between 0.15 and 1.1 μg l -1 and showed highest levels from late winter to spring. 3. Heterotrophic bacteria ranged between 75 and 250 × 10 6 l -1 with highest abundances in late winter/spring. Mean bacterial biovolumes showed considerable seasonal variation (0.05-0.31 μm 3 ). Largest biovolumes occurred in summer and this was the time of highest community biomass. 4. Heterotrophic nanoflagellates reached highest abundances in late summer (maximum 14 × 10 5 l -1 ). Their mean biovolume also exhibited considerable seasonal variation, ranging between 1.77 and 27.0 μm 3 , with largest size resulting in community biomass peaking in early summer. Ciliated protozoa were poorly represented and sparse. Phototrophic nanoflagellates were sparse in this lake; instead the phototrophic plankton was dominated by a small rod-shaped cyanobacterium which constituted the largest carbon pool in the system. It was common throughout the year, its biomass peaking in autumn. Its presence is discussed in relation to lake morphometry and light climate. 5. Heterotrophic flagellate grazing rates ranged from 6.78 bacteria cell -1 day -1 at 2°C to 11.8 bacteria cell -1 day -1 at 4°C. They remove around 2% of the bacterial carbon pool per day during summer and winter. 6. Nutrient levels were low and recorded in pulses. Dissolved and particulate organic carbon were also low, usually less than 3 mg l -1 and 600 μg l -1 , respectively. The carbon pools were derived from autochthonous sources. This lake system is driven by bottom-up forces and lacks top-down control, which fits into the picture currently seen for continental Antarctic lakes.